'Fear and loathing across party lines' (also) in Europe: Affective polarisation in European party systems. (22nd July 2019) - REILJAN, ANDRES
Abstract: Several scholars in the United States have recently addressed an increased partisan animosity between Democrats and Republicans, and have termed this phenomenon 'affective polarisation'. This surge in partisan affective polarisation is perceived to be highly problematic, as it has been found to have a negative impact on the functioning of the party system and even society at large. The aim of this article is to study the concept of affective polarisation in European party systems. It introduces the Affective Polarisation Index (API) that allows for measuring and comparing levels of affective polarisation also in multiparty systems. This novel measure is applied to 22 European democracies and the United States between 2005 and 2016. The results indicate that affective polarisation is acutely present in European party systems, as partisans are often extremely hostile towards competing parties. The most affectively polarised countries are in Central Eastern and Southern Europe where the degree of affective polarisation is notably higher than it is in the United States, while Northwestern European countries are more moderate in terms of partisan feelings. Further analysis reveals that affective polarisation is significantly correlated with ideological polarisation, but the relationship between the two appears to be conditional: in some Western European political systems ideological polarisation does not lead itself to strong interparty hostility, while in Central Eastern Europe a high degree of affective polarisation can be present even in ideologically centrist party structures. These findings validate the claim that ideological and affective polarisation are two distinct aspects of polarisation, and that the latter also merits additional attention.